Failure analysis of a plate heat exchanger used in a blast chiller. (October 2018) - Gagliardi, A.; Lanzutti, A.; Simonato, M.; Furlanetto, R.; Magnan, M.; Andreatta, F.; Fedrizzi, L.
Abstract: A stainless steel plate heat exchanger (PHE) was received to investigate the cause of its perforation in service leading to mixing of the fluids (water and refrigerant) circulating in the system. The heat exchanger was employed in a blast chiller using seawater subjected to a reverse osmosis process followed by salinization and sanitizing treatments. This study includes the analysis of water samples in different points of the system, a metallurgical characterization of the material of the plates, a study of the composition of corrosion products and an evaluation of the electrochemical behaviour of the material in the water samples extracted from the system. The study revealed that the material of the plates was perforated by a corrosion process due to the high level of chlorides present in the water employed in the blast chiller. Moreover, the localized attack of the stainless steel plates is enhanced by the peculiar geometry of the heat exchanger that leads to crevice corrosion in the region of the joint between overlapping plates. The results obtained in this work indicate that the failure is associated to the water treatment process performed upstream of the heat exchanger. Highlights: A stainless heat exchanger of a blast chiller exhibited perforation in service. Severe corrosion attack takes place on the side of the plate in contact with water. The attack is due to the accidental presence of strong oxidizers in the water. The attack is enhanced in the crevice between overlapping plates. Galvanic coupling between stainless steel and brazing material can favour the attack.